Cultural Heritage Protection as Post Conflict Diplomacy: A Framework for International Cooperation in Karabakh’s Reconstruction - Guluzada, Seljan; Safarova, Sabina; Osmanli, Osman (My University, 2026)
This project examined the use of cultural heritage protection as a strategy for post-conflict diplomacy, particularly focusing on the rebuilding efforts of Azerbaijan in the recently liberated Karabakh region. The goal of the project was to identify the ideal ways in which countries can cooperate in order to protect their cultural heritage while remaining sovereign states. Using the constructivist approach of international relations theory, the research used a qualitative multi-method design. A case comparison of heritage reconstruction in Mostar, Dubrovnik, and Bamiyan was conducted to determine what causes have been instrumental in gaining international legitimacy from factors such as transparency, institutional arrangement, and international participation. Following this, a stakeholder mapping approach was used to examine the institutional structure of Azerbaijan and its important stakeholders. From the findings of the research, it emerges that international legitimacy in this context is not an outcome of successful reconstruction in practical terms but rather of the institutional arrangements that allow for international validation. The research concludes that there is currently a “governance gap” in Azerbaijan in that there is good practice internally that is not sufficiently signaled internationally. The best solution is a “hybrid governance model” whereby a National Heritage Coordination Council is created along with involvement of UNESCO.